Hydrophonic: A Review on Plant without Soil (International Journal of Innovative Research in Engineering & Management, 2021)
Open field/soil-based agriculture has faced significant  difficulties since the dawn of civilization, the most significant of  which is a reduction in per capita land supply. In 1960, when the  population of the planet was 3 billion people, per capita land  was 0.5 hectares; currently, with 6 billion individuals, it's really  only 0.25 hectares, and by 2050, it will be 0.16 hectares. As a  consequence of increased urbanization and industrialization, and  also cultural group melting, or icebergs (as just a planet warms),  arable land under cultivation will continue to diminish. Fertility  of the land comes up again. Food production is threatened by  inadequate water management and massive water waste, as well  as a decrease in ground water levels. In the context of traditional  soil-based agriculture.In such conditions, feeding the whole  population will become difficult in the near future. Only the  open field method of agricultural production is used by the  people. Naturally, soilless culture is gaining in popularity. In the  current situation, to meet these difficulties Plants are grown  without soil in soil-less cultivation. Improved water and space  Using soil-less culture to save food production techniques has  shown some encouraging outcomes all around the world.
Keywords: Agriculture; Crops; Hydrophonic; Soil